UiTM Health Festival 2024: empowering communities through health awareness and action - Khalil, Asma’; Mat Ruzlin, Aimi Nadira; Azhar, Zahir Izuan; Xin Wee, Chen (Faculty of Medicine, 2025)
On October 12th to 13th, 2024, the Department of Public Health Medicine, Faculty of Medicine, hosted its annual Health Festival—a series of health carnivals across Selangor aimed at promoting community health and wellness. Led by fourth-year medical students, this initiative emphasized awareness, prevention, and community engagement.